2016
DOI: 10.1177/1759091416668430
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 Promotes Oligodendrogenesis and Myelination in the Adult Central Nervous System and After Lysolecithin-Induced Demyelination

Abstract: A key aim of therapy for multiple sclerosis (MS) is to promote the regeneration of oligodendrocytes and remyelination in the central nervous system (CNS). The present study provides evidence that the vitamin K-dependent protein growth arrest specific 6 (Gas6) promotes such repair in in vitro cultures of mouse optic nerve and cerebellum. We first determined expression of Gas6 and TAM (Tyro3, Axl, Mer) receptors in the mouse CNS, with all three TAM receptors increasing in expression through postnatal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 58 publications
3
36
0
1
Order By: Relevance
“…While Axl –/– mice show no differences in the number of myelinated axons in the corpus callosum at 3‐weeks recovery, significantly fewer myelinated axons are observed in DKO relative to WT mice, suggesting that deletion of Axl alone does not directly impair remyelination (Hoehn et al, ). The ability of Axl –/– mice to efficiently remyelinate axons at 3‐weeks recovery while Gas6 –/– and DKO mice show impairment in remyelination provide further support of a role for Gas6‐Tyro3 signaling in remyelination (Akkermann et al, ; Goudarzi et al, ; Prieto, O'Dell, Varnum, & Lai, ; Prieto et al, ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…While Axl –/– mice show no differences in the number of myelinated axons in the corpus callosum at 3‐weeks recovery, significantly fewer myelinated axons are observed in DKO relative to WT mice, suggesting that deletion of Axl alone does not directly impair remyelination (Hoehn et al, ). The ability of Axl –/– mice to efficiently remyelinate axons at 3‐weeks recovery while Gas6 –/– and DKO mice show impairment in remyelination provide further support of a role for Gas6‐Tyro3 signaling in remyelination (Akkermann et al, ; Goudarzi et al, ; Prieto, O'Dell, Varnum, & Lai, ; Prieto et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…The importance of both Gas6 and Axl signaling has been well documented in the CNS during autoimmune and demyelinating conditions such as MS and in mice during myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) and the cuprizone toxicity model (Akkermann et al, 2017;Binder et al, 2008;Goudarzi, Rivera, Butt, & Hafizi, 2016;Gruber et al, 2014;Hoehn et al, 2008;Shankar et al, 2006;Tsiperson, Li, Schwartz, Raine, & Shafit-Zagardo, 2010;Weinger et al, 2011;Weinger, Omari, Marsden, Raine, & Shafit-Zagardo, 2009). Our study of TAM proteins in MS lesions showed elevated levels of soluble Axl and MerTK, and increased levels of proteins associated with Axl and MerTK solubilization that is not seen in normal appearing white matter from the same individuals (Weinger et al, 2009).…”
mentioning
confidence: 99%
“…( Figure 2B). In addition to its role in viral entry, GAS6 promotes oligodendrogenesis and myelination in the adult nervous system (52) and acts as a neurotrophic factor during hippocampal development (53). NECTIN2 is necessary for neuronal and glial survival (54).…”
Section: Maternal Immune Activation Induces Brain Transcriptomic Chanmentioning
confidence: 99%
“…Выявлено влияние витамина K на когнитивную функцию, его положительные эффекты при болезни Альцгеймера. Среди ВK-зависимых белков наибольшими нейротропными свойствами, реализуемыми в структурах нервной системы, обладает Gas6: он участвует в процессах миелинизации, хемотаксисе, митогенезе, клеточном росте, регуляции функции олигодендроцитов, шванновских клеток, микроглии [22]. Интересно, что экспрессия гена белка Gas6 наблюдается еще на ранних стадиях эмбриогенеза, что указывает на его роль в развитии нервной системы плода [21].…”
Section: эффекты витамина Kunclassified